Endoderm and Hepatic Progenitor Cells Engraft in the Quiescent Liver Concurrent with Intrinsically Activated Epithelial-to-Mesenchymal Transition. (2nd March 2021) - Fagg, W. Samuel; Liu, Naiyou; Patrikeev, Igor; Saldarriaga, Omar A.; Motamedi, Massoud; Popov, Vsevolod L.; Stevenson, Heather L.; Fair, Jeffrey H.
Stem cell transplantation to the liver is a promising therapeutic strategy for a variety of disorders. Hepatocyte transplantation has short-term efficacy but can be problematic due to portal hypertension, inflammation, and sinusoidal thrombosis. We have previously transplanted small mouse endoderm progenitor (EP) cells to successfully reverse a murine model of hemophilia B, and labeling these cells with iron nanoparticles renders them responsive to magnetic fields, which can be used to enhance engraftment. The mechanisms mediating progenitor cell migration from the sinusoidal space to the hepatocyte compartment are unknown. Here we find human EP and hepatic progenitor (HP) cells can be produced from human embryonic stem cells with high efficiency, and they also readily uptake iron nanoparticles. This provides a simple manner through which one can readily identify transplanted cells in vivo using electron microscopy, shortly after delivery. High resolution imaging shows progenitor cell morphologies consistent with epithelial-to-mesenchymal transition (EMT) mediating invasion into the hepatic parenchyma. This occurs in as little as 3 h, which is considerably faster than observed when hepatocytes are transplanted. We confirmed activated EMT in transplanted cells in vitro, as well as in vivo 24 h after transplantation. We conclude that EMT naturally occurs concurrent with EP and HP cell engraftment, which may mediate the rate, safety, and efficacy of early cell engraftment in the undamaged quiescent liver.